2022
DOI: 10.1002/ece3.9652
|View full text |Cite
|
Sign up to set email alerts
|

The response of litter decomposition to extreme drought modified by plant species, plant part, and soil depth in a temperate grassland

Abstract: Plant litter decomposition is a key ecosystem process in carbon and nutrient cycling, and is heavily affected by changing climate. While the direct effects of drought on decomposition are widely studied, in order to better predict the overall drought effect, indirect effects associated with various drought-induced changes in ecosystems should also be quantified. We studied the effect of an extreme (5-month) experimental drought on decomposition, and if this effect varies with two dominant perennial grasses, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…One of the ways in which a dominance change from Festuca to Stipa may have a considerable impact relates to decomposition and, consequently, carbon and nutrient cycling. In a recent study, Seres et al (2022) found that leaf and root litter from Festuca vaginata is decomposed by the local microbial community at a faster rate than the respective plant parts from Stipa borysthenica . In the case of leaves, this is due to higher lignin and lower N content in Stipa , making the litter from this species harder to break down.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ways in which a dominance change from Festuca to Stipa may have a considerable impact relates to decomposition and, consequently, carbon and nutrient cycling. In a recent study, Seres et al (2022) found that leaf and root litter from Festuca vaginata is decomposed by the local microbial community at a faster rate than the respective plant parts from Stipa borysthenica . In the case of leaves, this is due to higher lignin and lower N content in Stipa , making the litter from this species harder to break down.…”
Section: Discussionmentioning
confidence: 99%
“…In other places, climate warming is predicted to increase the frequency and intensity of droughts, which could in turn reduce decomposition by limiting the biological activity of decomposer organisms, as has been shown in temperate grasslands (Vogel et al 2013;Walter et al 2013). Therefore, in warmer systems and systems with high variability in precipitation (e.g., savannahs), the warming response is likely to depend strongly on concurrent moisture conditions (Aerts 1997;Seres et al 2022). Our study should lead to a better understanding of the interaction between the prevailing macro-environmental conditions and the changes in decomposition caused by warming.…”
Section: Introductionmentioning
confidence: 99%
“…2013). Therefore, in warmer systems and systems with high variability in precipitation (e.g., savannahs), the warming response is likely to depend strongly on concurrent moisture conditions (Aerts 1997; Seres et al . 2022).…”
Section: Introductionmentioning
confidence: 99%